3D Differentiation Of Mammosphere Derived Macaca fascicularis’s Mammary Stem Cells - silmi mariya (Stem Cell Research and Development Center, Universitas Airlangga, 2019)
The mammary gland contains adult stem cells that are capable of self-renewal. This population plays an important role in the development of mammary gland and breast cancer pathogenesis. The studies of mammary stem cells are limited due to the difficulty to acquire and expand adult stem cell population in an undifferentiated state. In this study, we developed mammosphere cultures of nulliparous cynomolgus monkeys (Macaca fascicularis; Mf) as a culture system to enrich mammary stem cells. This species has similarity of mammary gland structure as humans including anatomy, developmental stages, and lobule profile of mammary gland. The use of stem cells from primate animals is essential to bridge the knowledge gaps resulting from stem cell research using rodents for clinical trials in human. Small samples of mammary tissues were collected by surgical biopsy; cells were cultured as monolayer and cryopreserved. Cryopreserved cells were cultured into mammospheres, and the expression of markers for mammary stem cells was evaluated using qPCR. Cells were further differentiated with 3D approaches to evaluate morphology and organoid budding. The study showed that mammosphere culture resulted in an increase in the expression of mammary stem cell markers with each passage. The 3D differentiation in matrigel allowed for organoid formation. Mammary gland stem cells have been successfully differentiated which characterized by CSN2 marker expression and differentiation regulators marker STAT5 and GATA3. The results indicate that mammospheres can be successfully developed derived from breast tissue of nulliparous Mf collected via surgical biopsy. As the mammosphere allows for enrichment of mammary stem cell population, the findings also suggest that a 3-dimensional system is efficient as in-vitro model to study mammary stem cells and a useful system to study mammary differentiation in regards to cancer prevention.